Solve this inequality: (t-2)(t+3)/(t-4)>=0.

I did it using a factor table, and I got the results -3<=x<=2 and x>=4, but the answer says it should be x>4 instead, and I am not sure how they go that. Thanks in advance!

Solve this inequality: (t-2)(t+3)/(t-4)>=0.

I did it using a factor table, and I got the results -3<=x<=2 and x>=4, but the answer says it should be x>4 instead, and I am not sure how they go that. Thanks in advance!

I did it using a factor table, and I got the results -3<=x<=2 and x>=4, but the answer says it should be x>4 instead, and I am not sure how they go that. Thanks in advance!

- little_dragon
**Posts:**197**Joined:**Mon Dec 08, 2008 5:18 pm-
**Contact:**

Seaweed09 wrote:Solve this inequality: (t-2)(t+3)/(t-4)>=0.

I did it using a factor table, and I got the results -3<=x<=2 and x>=4, but the answer says it should be x>4 instead, and I am not sure how they go that. Thanks in advance!

U cant divide by 0!

if t=4 then t-4=0